Sarcophagodes duodecima sp. nov., a new small araphid fossil diatom (Bacillariophyceae) from Lower to Middle Pleistocene sediments of Japan - Naya, Tomonori; Mizuno, Kiyohide (Phytotaxa, 2021)
A new fossil diatom species, Sarcophagodes duodecima, is described from the Lower to Middle Pleistocene Karato Formation of Himeshima Island, western Japan, based on detailed morphological observation of valves using light and scanning electron microscopes. This new species is characterized by a smaller valve length range, a wide lanceolate central area, shorter striae on the valve face, and longer striae on the mantle than other members of the genus. The new species was also found in the Lower Pleistocene Bushi Formation, central Japan, suggesting that S. duodecima sp. nov. was widely distributed in Japan during Early Pleistocene time. The species composition in the sample chosen as type suggests that the new fossil species occupied a brackish-water habitat. Differences in morphological features from closely related taxa are discussed.